MARKERS OF CONNECTIVE TISSUE METABOLISM IN PATIENTS WITH DIABETIC ARTHROPATHY (World Science, 2020)
The aim of study was to investigate markers of connective tissue metabolism (COMP level) and indicators that reflect the synthetic and catabolic phases of the metabolism of the main components of connective tissue - collagen and glycosaminoglycans in patients with diabetic arthropathy.The study involved 87 patients with diabetes. Patients were examined using a visual analogue scale of the Leken index and WOMAK. Cartilage oligomeric matrix Protein (COMP) was determined using enzyme immunoassay.Results. The presence of diabetic arthropathy was detected in 78% of patients with type 1 diabetes and in 80% of patients with type 2 diabetes. In the vast majority of patients, the joints of the upper extremities were involved in the pathological process. A direct correlation was established between the presence of arthropathy and the COMP level (r = 0.76, p = 0.001), the Leken index (r = 0.76, p = 0.001), YOUR scale (r = 0.88 , p = 0.001) and WOMAK (R = 0.88, p = 0.001). Patients with type 1 diabetes with joint damage are characterized by a compensatory increase in the synthesis of subchondral bone in response to increased collagen breakdown. For patients with type 1 diabetes with joint damage is characterized by a compensatory increase in subchondral bone synthesis in response to increased collagen breakdown.Conclusions: The results suggest that arthropathy in patients with type 1 and type 2 diabetes is characterized by an increase in the cartilage degradation marker in direct proportion to the severity and number of affected joints.